If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + 3(3x + 4) = 4 Reorder the terms: 2(-1 + x) + 3(3x + 4) = 4 (-1 * 2 + x * 2) + 3(3x + 4) = 4 (-2 + 2x) + 3(3x + 4) = 4 Reorder the terms: -2 + 2x + 3(4 + 3x) = 4 -2 + 2x + (4 * 3 + 3x * 3) = 4 -2 + 2x + (12 + 9x) = 4 Reorder the terms: -2 + 12 + 2x + 9x = 4 Combine like terms: -2 + 12 = 10 10 + 2x + 9x = 4 Combine like terms: 2x + 9x = 11x 10 + 11x = 4 Solving 10 + 11x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 11x = 4 + -10 Combine like terms: 10 + -10 = 0 0 + 11x = 4 + -10 11x = 4 + -10 Combine like terms: 4 + -10 = -6 11x = -6 Divide each side by '11'. x = -0.5454545455 Simplifying x = -0.5454545455
| e^14x=110 | | h=-16t^2+24t | | 0.007x^2+0.02x-150=0 | | 2x^2+8x-15= | | 9z+5=11z-5 | | 10-4r=-2(3r+5)+7r | | 2x-x+6x+5=41 | | 5(-4)=-3x+44 | | -6(10+p)=-150 | | 20x-x^2-150=0 | | 10+6x-4=26+2x | | -7w+4=10 | | 8x+24+2x+96=180 | | -2n+4n-7=0 | | -12+x=-3 | | 3y-6=6(y-2) | | -5-4x-2x=-7 | | 12+3x-3=15-4x | | (12x^2)+x+4=0 | | 3(5x-7)=5(3x+4) | | 3x+6x-6=18 | | 4x+4+2x+38=180 | | 4z-13=3 | | 2x+4=5(x+1)3-(x+2) | | 12x^4=18x^2 | | x-9y+7=0 | | 7x+2x-7=3 | | 10x-5.3=1.2 | | .5r+4=20 | | -63=-12.5t-4.9t^2 | | 4+6x-5=43 | | 4(b+5)=2(4b+5) |